Women In Science - The Sun, (2008)
For the third year running L'Oreal Malaysia will grant fellowship awards to three deserving young female researchers to pursue scientific projects in the country The L'Oreal Malaysia For Women in Science Fellowships is a corporate commitment to provide encouragement and support to women in the field of science.